2013
DOI: 10.1542/peds.2013-0279
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial of Exothermic Mattresses for Preterm Newborns in Polyethylene Bags

Abstract: BACKGROUND AND OBJECTIVE: Hypothermia on admission to the NICU is associated with increased mortality in preterm infants. Many newborns are hypothermic on admission despite using polyethylene bags (PBs). Using exothermic mattresses (EMs) in addition to PBs may reduce hypothermia but increase hyperthermia. We wished to determine whether placing preterm newborns in PBs on EMs in the DR results in more infants with rectal temperature outside the range 36.5 to 37.5°C on NICU admission. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 27 publications
1
53
0
2
Order By: Relevance
“…Initial stabilization should be performed with the baby wrapped in a polyethylene bag under a radiant warmer [125]. Addition of an exothermic mattress may increase the risk of overheating [126]. Warming and humidification of gases used for stabilization may also improve temperature [127].…”
Section: Monitoring and Supportive Carementioning
confidence: 99%
“…Initial stabilization should be performed with the baby wrapped in a polyethylene bag under a radiant warmer [125]. Addition of an exothermic mattress may increase the risk of overheating [126]. Warming and humidification of gases used for stabilization may also improve temperature [127].…”
Section: Monitoring and Supportive Carementioning
confidence: 99%
“…Various combinations of these strategies may be reasonable to prevent hypothermia in infants born at less than 32 weeks of gestation (Class IIb, LOE B-R, B-NR, C-LD). Compared with plastic wrap and radiant warmer, the addition of a thermal mattress, [66][67][68][69][70] warmed humidified gases, 71,72 and increased room temperature plus cap plus thermal mattress 55,57,59,73 were all effective in reducing hypothermia. For all the studies, hyperthermia was a concern, but harm was not shown.…”
Section: Nrp 599mentioning
confidence: 99%
“…For the important outcome of hyperthermia (temperature greater than 38.0°C) at admission, we have identified lowquality evidence (downgraded for serious risk of bias) from the same randomized controlled trial 102 For the important outcome of hyperthermia (temperature greater than 38.0°C) at admission, we identified low-quality evidence (downgraded for serious risk of bias) from the same observational study 108 showing no harm (OR, not estimable).…”
Section: Thermal Mattress Plus Plastic Wrap Plus Radiant Warmer (I) Vmentioning
confidence: 99%